BIM adoption in the AEC/FM industry – the case for issuing building permits - Ullah, Kaleem; Raitviir, Christopher; Lill, Irene; Witt, Emlyn (International Journal of Strategic Property Management, 2020)
BIM adoption is a complex process and relatively little information exists on the BIM adoption processes of public authorities. This research aims to address this gap by examining how a contemporary public authority is approaching BIM adoption for their building permitting process. Firstly, a systematic literature review was carried out to understand extant descriptions of BIM adoption processes and the factors affecting adoption success. This resulted in the derivation of a generic BIM adoption process and the classification of factors that affect BIM adoption with reference to the Technology Organization and Environment (TOE) framework. The case of the BIM adoption process and the factors affecting its implementation in a contemporary public authority were then analysed in terms of the generic adoption process and factor classification derived from the literature. The findings reveal the planning strategies and execution steps for BIM adoption and the factors affecting them. This study provides a systematic approach to investigating BIM adoption in a public authority. It contributes to the understanding of BIM adoption processes and factors affecting them and is anticipated to be useful for AEC/FM professionals in understanding and facilitating successful BIM adoption.